Small Motion Detection and Non-Contact Vital Signs Monitoring with Continuous Wave Doppler Radars - Seflek, Ibrahim; Acar, Yunus Emre; Yaldiz, Ercan (Elektronika ir Elektrotechnika, 2020)
Radars have become devices that one can come across in any environment at any moment. This means that they enter to all areas of life and even in the field of medicine and will be used more intensively in the future. Especially, the attention has been drawn to that they are suitable for the non-contact vital signs monitoring. In this study, two radar structures operating at 24 GHz (Radar 1) and 2.4 GHz (Radar 2) frequencies are used. Radar 1 structure is created on a printed circuit board (PCB), whereas Radar 2 is obtained by combining discrete components. The 8.5 mm movement performed with the aid of a test mechanism is detected by two radars with percentage errors (PEs) of 2.58% and 6.23%, respectively. For the 0.25 Hz vibration frequency, the error is the same for both radars and is 2.4 %. In measurements taken from a healthy human subject, Radar 1 finds a respiration rate with 1.85 % of PE and heart beat rate with 6.17 % of PE. In Radar 2, these values are 2.35 % and 8.24 %, respectively. From the measurement results, it is seen that the resolution of Radar 1 is better than that of Radar 2. The results also indicate that small motion detection and vital signs monitoring are carried out successfully.